Mesenchymal Stem Cell-Derived Exosomes: Immunomodulatory Evaluation in an Antigen-Induced Synovitis Porcine Model - Casado, Javier G.; Blázquez, Rebeca; Vela, Francisco Javier; Álvarez, Verónica; Tarazona, Raquel; Sánchez-Margallo, Francisco Miguel (Frontiers in Veterinary Science, 2017)
Synovitis is an inflammatory process associated with pain, disability and discomfort which is usually treated with anti-inflammatory drugs or biological agents. Mesenchymal Stem Cells (MSCs) have been also successfully used in the treatment of inflammatory-related diseases such as synovitis or arthritis. In the last years, the exosomes derived from MSCs have become a promising tool for the treatment of inflammatory-related diseases and their therapeutic effect is thought to be mediated (at least in part) by their immunomodulatory potential. In this work we aimed to evaluate the anti-inflammatory effect of these exosomes in an antigen-induced synovitis animal model. To our knowledge, this is the first report where exosomes derived from MSCs have been evaluated in an animal model of synovitis. Our results demonstrated a decrease of synovial lymphocytes together with a downregulation of TNF-α transcripts in those exosome-treated joints. These results support the immunomodulatory effect of these exosomes and point out that they may represent a promising therapeutic option for the treatment of synovitis.